Prevalence of anemia and associated factors among adult hypertensive patients in Referral Hospitals, Amhara Regional State - Yibeltal Yismaw Gela; Daniel Gashaneh Belay; Dagmawi Chilot; Amare Agmas Andualem; Desalegn Anmut Bitew; Deresse Sinamaw; Habitu Birhan Eshetu; Abdulwase Mohammed Seid; Wudneh Simegn; Anteneh Ayelign Kibret; Mohammed Abdu Seid; Mengistie Diress (Scientific Reports, 2023)
Abstract Anemia is a risk factor for adverse cardiovascular disease outcomes in hypertensive patients. Chronic anemia increases preload, reduces afterload, and leads to increased cardiac output in hypertension patients. In the long term, this may result in maladaptive left ventricular hypertrophy, which in turn is a well-recognized risk factor for cardiovascular disease outcomes and all-cause mortality in hypertension. Low hemoglobin and hematocrit levels might be strongly indicate hypertensive end-organ damage, specifically kidney failure. Therefore, this study determined the prevalence of anemia and associated factors among hypertensive patients in Referral Hospitals, Amhara Regional State, Ethiopia, in 2020. An institution-based cross-sectional study was conducted in Amhara Regional Referral Hospitals from February 20 to April 30, 2020. Random and systemic sampling techniques were used to select 428 study participants. Data were entered and coded in to Epi data version 3.0 and then exported into STATA 14 for analysis. In bivariable logistic regression, variables with a p-value of < 0.25 were included in multivariable logistic regression. Using a 95% confidence interval, variables having a p-value ≤ 0.05 in multivariable logistic regression were declared as statistically significant variables. In this study, a total of 428 study participants were involved with 99.5% response rate. The prevalence of anemia among hypertensive patients was 17.6%, with a 95% CI (14.3–21.5%). Estimated glomerular filtration rate (eGFR) < 90 ml/min (AOR = 2.77, 95% CI 1.56- 4.92)], duration of hypertension (HTN) ≥ 5 years (AOR = 2.37, 95% CI 1.36–4.15), uncontrolled blood pressure (AOR = 1.91, 95% CI 1.08–3.35), and higher pulse pressure (AOR = 1.05 (95% CI 1.02–1.08) were significantly associated with anemia. Nearly one out of five hypertensive patients had anemia. Impaired estimated glomerular filtration rate, duration of HTN, blood pressure status, and pulse pressure were the independent predictors of anemia among hypertensive patients. Screening hemoglobin level at a regular interval is recommended for the hypertensive patients to take an appropriate intervention.